GLUCAGON LIKE PEPTIDE-1 REDUCES RAISED INTRACRANIAL PRESSURE. Issue 12 (15th November 2016) - Botfiled, Hannah; Ulhdall, Maria; Mitchell, James; Hagen, Snorre; Gonzalez, Ana Maria; Jensen, Rigmor; Sinclair, Alex
Abstract : Current therapies for reducing raised intracranial pressure (ICP) in conditions such as idiopathic intracranial hypertension (IIH) have limited efficacy and tolerability; therefore there is an urgent need to develop novel therapies. Glucagon-like peptide-1 receptor (GLP-1R) agonists are used therapeutically to treat diabetes and promote weight loss but have also been shown to affect fluid homeostasis in the kidney. The GLP-1R is also present in the choroid plexus, therefore we investigated whether Exendin-4, a GLP-1R agonist, is able to modulate cerebrospinal fluid (CSF) secretion at the choroid plexus and subsequently reduce ICP. We used in vitro models of the choroid plexus to demonstrate the presence of the GLP-1R and, after Exendin-4 treatment, showed a two fold increase in cAMP, a downstream signaling molecule. We also determine that treatment with Exendin-4 reduces Na+ K+ ATPase activity, a key regulator of CSF secretion. Finally, we demonstrate that administration of Exendin-4 in normal and raised ICP (hydrocephalic) rats significantly reduces ICP. These findings provide the first proof of concept that GLP-1R agonists can affect CSF secretion and ICP. Repurposing existing GLP-1 drugs may represent a novel therapeutic strategy for conditions of raised ICP including IIH, hydrocephalus and traumatic brain injury.